The Philosophy of Science Education on Children's Character Education - Setyawan, Alif; Novikasari, Ifada (International Proceedings of Nusantara Raya, 2024)
The shift towards a more holistic education reflects a paradigm shift in the education system which recognizes that student success is not only measured by academic achievement, but also by the development of their character and social skills. Holistic education emphasizes the importance of educating children holistically, involving emotional, social and moral aspects. This research explores the impact of philosophy of science education on children's character education, a concept that is often ignored in formal curricula. The surprising phenomenon that was raised was that most educational systems focus more on cognitive and academic aspects, while character development based on philosophical principles is often neglected. This research was conducted in elementary schools, with the aim of understanding how the application of the philosophy of science can strengthen children's character education. The method used is qualitative research with a case study approach, involving in-depth interviews with teachers, students and parents. The results of the research show that education in the philosophy of science, especially involving an understanding of ethics, logic and epistemology, can significantly shape children's character who is more critical, ethical and wise. Character education based on philosophical foundations provides children with a deeper frame of mind in understanding moral and ethical values.